'Difficult' representations. Visual art engaging with the refugee crisis. Issue 3 (3rd July 2019) - Yalouri, Eleana
Abstract : This paper discusses visual engagements with the refugee issue in Greece and beyond from 2015 to 2017. Drawing mostly, but not only on visual art works, I investigate the extent to which contemporary art can operate as a means of criticising stereotypes and clichés concerning the refugee crisis and its representations, as well as the extent to which it can intervene and act subversively. Since most of the art projects I discuss here use specific objects as a visual means of approaching their subject matter, I also examine the ways in which these objects operate in representing the refugee crisis.